2011
DOI: 10.4049/jimmunol.1002864
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in NF-κB Inducing Kinase Is Associated with Mortality in Septic Shock

Abstract: We tested the hypothesis that single nucleotide polymorphisms (SNPs) within genes of the NF-κB pathway are associated with altered clinical outcome of septic shock patients. We genotyped 59 SNPs in the NF-κB pathway in a discovery cohort of septic shock patients (St. Paul’s Hospital [SPH], N = 589), which identified the C allele of rs7222094 T/C within MAP3K14 (NF-κB inducing kinase; NIK) associated with increased 28-d mortality (uncorrected p = 0.00024, Bonferroni corrected p = 0.014). This result was replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
(73 reference statements)
1
34
0
1
Order By: Relevance
“…T HERE is wide variability regarding the outcome in severe sepsis, which in part may be caused by genetic variations. [1][2][3] A potential candidate for such variations is the gene encoding nuclear factor-κB and activator protein-1 (NF-κB1), because the ubiquitous transcription factor NF-κB1 binds to recognition elements in the promoter regions of several genes encoding the innate immune and the coagulation system. The nuclear factor-κB family comprises five proteins, NF-κB1, NF-κB2, RelA, RelB, and c-Rel.…”
Section: Discussionmentioning
confidence: 99%
“…T HERE is wide variability regarding the outcome in severe sepsis, which in part may be caused by genetic variations. [1][2][3] A potential candidate for such variations is the gene encoding nuclear factor-κB and activator protein-1 (NF-κB1), because the ubiquitous transcription factor NF-κB1 binds to recognition elements in the promoter regions of several genes encoding the innate immune and the coagulation system. The nuclear factor-κB family comprises five proteins, NF-κB1, NF-κB2, RelA, RelB, and c-Rel.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our lab and by other study groups has shown that genetic variation within inflammatory genes is associated with outcome in sepsis and septic shock [18][19][20][21][22][23][24][25][26] as well as with the levels of cytokines [27] . We have shown TNFAIP2 inhibits basal NF-κB luciferase activity with a more pronounced effect in the rs8126 G allele.…”
Section: Discussionmentioning
confidence: 72%
“…In the innate immune response, haplotype clades in the integrative inflammatory cytokine IL-6 increase the risk of organ failure and death in those who present with a severe infection [39], while polymorphisms in IL-8, protein C and NFκB-inducing kinase are associated with increased and more severe organ failure complicating septic shock [40,41,42,43]. Because treatment of septic shock is largely supportive, aimed at early broad-spectrum (often nonspecific antibiotics), normalizing blood pressure and organ perfusion [25], polymorphisms in genes active in the vasopressor response are also associated with increased risk of organ dysfunction.…”
Section: Sepsis In the Era Of The Meta-genomementioning
confidence: 99%